2020
DOI: 10.1590/0004-282x20190188
|View full text |Cite
|
Sign up to set email alerts
|

Medical management after subthalamic stimulation in Parkinson’s disease: a phenotype perspective

Abstract: Subthalamic nucleus deep brain stimulation (STN DBS) is an established treatment that improves motor fluctuations, dyskinesia, and tremor in Parkinson’s disease (PD). After the surgery, a careful electrode programming strategy and medical management are crucial, because an imbalance between them can compromise the quality of life over time. Clinical management is not straightforward and depends on several perioperative motor and non-motor symptoms. In this study, we review the literature data on acute medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 46 publications
0
4
0
3
Order By: Relevance
“…After deep brain stimulation (DBS) of the subthalamic nucleus (STN), the levodopa equivalent daily dose (LEDD) can usually be reduced by 30–50% for best motor outcome (Fasano et al 2016). One study demonstrated that of 150 patients after STN-DBS, even 7% were free from medication after 3 years (Bertholo et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…After deep brain stimulation (DBS) of the subthalamic nucleus (STN), the levodopa equivalent daily dose (LEDD) can usually be reduced by 30–50% for best motor outcome (Fasano et al 2016). One study demonstrated that of 150 patients after STN-DBS, even 7% were free from medication after 3 years (Bertholo et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…The complete discontinuation of dopaminergic medication after STN-DBS is usually not possible, because the lack of dopamine in the limbic system and associative circuits can lead to apathy and depression (Fasano et al 2016; Bertholo et al 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Tal procedimento faz com que o dispositivo DBS ative estruturas cerebrais por meio da implantação de eletrodos em núcleos específicos, principalmente subtalâmicos (STN) e o globo pálido interno (GPi). Deste modo, são utilizados para tratar distúrbios neurológicos e psicológicos associados a DP, além de reduzir a administração medicamentosa e superar as complicações motoras acarretadas à terapia dopaminérgica na DP avançada (ARTEN & HAMDAN, 2020) (BERTHOLO, et al, 2020).…”
Section: Tratamento Cirúrgico -Deep Brain Stimulation (Dbs)unclassified
“…A voltagem dos estímulos gerados pelo eletrodo é outro fator que deve ser minuciosamente ajustado, já que os sinais e sintomas da DP que levaram ao processo cirúrgico são individuais, assim como a resposta ao tratamento. Deste modo, é de extrema importância o acompanhamento médico a longo prazo após a aplicação do DBS, sabendo que o desequilíbrio entre os eletrodos pode gerar comprometimentos graves de funções motoras e não motoras deste paciente (BERTHOLO, et al, 2020).…”
Section: Tratamento Cirúrgico -Deep Brain Stimulation (Dbs)unclassified
See 1 more Smart Citation